Transformerless resonant converter driving multiple ozone chambers for high flow rates - Amjad, Muhammad (2013)
Ozone gas (O3) is increasingly used as a bleaching agent due to its strong oxidising properties and less harmful to the environment. The most feasible method to generate O3 is to connect high-voltage of several kV, high-frequency of about tens of kHz power supply across a Dielectric Barrier Discharge (DBD) chamber. Commonly, a resonant power supply with the ferrite transformer is used. However, the presence of the transformer increases the cost and footprint, while reduces the efficiency of the ozone generator. To overcome these deficiencies, this work proposes a design and implementation of an ozone power supply based on transformerless resonant converter. A standard full-bridge inverter is coupled to a resonant tank circuit, i.e. LC and LCL to achieve the required high voltage. The LCL exhibits a double resonance phenomenon resulting in very high voltage gain (above 150). Consequently, the power supply is capable of delivering sufficient potential to the chamber, even if the source voltage is below 20 V. Experimental measurements show that the efficiency of the proposed generator is 92%, while the maximum ozone concentration achieved 8.0 g/m3 at a flow rate of 1.0 L/min. This performance is much higher than the existing transformer based resonant converters. This thesis also introduces the concept of ozone generation using multiple chambers. The objective is to maintain a high O3 concentration at high flow rates. To realise the idea, the same LCL transformerless ozone generator is used to drive three ozone chambers in parallel. The results indicate that the achieved ozone concentration is three times higher than the output of a single chamber. Furthermore, a closed loop regulation to maintain a stable and constant chamber’s output voltage is designed. Another contribution of this work is the introduction of a simple and effective method to characterise the DBD chamber parameters. Traditionally, Lissajous figures are employed to estimate the values of the chamber’s resistor and capacitor. However, this method proves unsatisfactory at high frequencies. Using the proposed method, the chamber parameters can be determined accurately at various frequencies.